From Healing the Whole Person: An Argument for Therapeutic Touch as a Complement to Traditional Medical Practice - Marlene B. Huff; Kimberly K. McClanahan; Hatim A. Omar (The Scientific World Journal)
The growing popularity and use of therapeutic touch (TT) is an issue that has generated controversy and concern within the medical community. While anecdotal and traditional scientific evidence suggest that TT would be an advantageous addition for clinics and hospitals to include in their armamentarium of complementary interventions within the realm of traditional medicine, TT has not become widely available in the U.S. One reason for the lack of availability may be the dearth of conclusive scientific support for TT's efficacy and, therefore, its inclusion in clinic and hospital treatment planning would give it the appearance of legitimate practice, which it may not yet deserve. Whether or not deserved, if TT were added to hospital and clinic treatment protocols without substantial scientific support, it would be thought to have the implicit support of the scientific community, at which point the question of its efficacy would be moot in the minds of many people; thus patients would utilize it, because they believe it works rather than because it works. Since TT has not yet been scientifically proven as per Western standards, leaders of the health care community are likely wary of lending support to TT at this time. If TT can be found to be a scientifically sound therapeutic technique, then it will be more readily accepted in the health care community. This paper reviews TT.